Copyright Legal Responsibility for Illustrated Literary Works (Comics) Published on Online Sites Without Author's Permission - Rory Jeff Akyuwen; Muchtar Anshary Hamid Labetubun; Alvian Febriawan Pane (SASI, 2023)
Introduction: Comics are also creations that are equally important in the copyright protection system. This is because the importance of protecting comics is not only related to the development of human culture and civilization, as well as supporting economic progress, but can also stimulate the creativi ty of creators with the existence of a comic copyright protection law.